2022
DOI: 10.28982/josam.903246
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on the quality of life of the elderly population

Abstract: Background/Aim: The elderly population were most exposed to lockdowns worldwide. Lockdown causes many disorders in people's daily routines, and the elderly suffer the most from these disorders. Our aim is to investigate the impact of the COVID-19 epidemic, which we do not know how long will last, on the psychological status and quality of life (QOL) of the elderly population. Methods: A total of 226 male and female volunteers over the age of 65 years and with a score above 21 in the Minimental test were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In line with the results of the present study, the findings of the study by Ahi et al indicated that the elderly with COVID-19 had a lower quality of life than the noninfected elderly. Also, there was a statistically significant difference between the score of the quality of life of the elderly before and during the COVID pandemic, so that the quality of life of the elderly during the pandemic was reported to be lower than before the pandemic [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In line with the results of the present study, the findings of the study by Ahi et al indicated that the elderly with COVID-19 had a lower quality of life than the noninfected elderly. Also, there was a statistically significant difference between the score of the quality of life of the elderly before and during the COVID pandemic, so that the quality of life of the elderly during the pandemic was reported to be lower than before the pandemic [16].…”
Section: Discussionmentioning
confidence: 93%
“…The elderly are at a greater risk of severe illness and death after contracting COVID-19, and this issue makes them prone to increasing psychological problems and reducing the quality of life [15]. Studies have shown that the quality of life of the elderly has decreased during the COVID-19 pandemic compared to before the pandemic [16,17].…”
Section: Introductionmentioning
confidence: 99%